Application of organic-inorganic hybrid light detection material in preparation of photoelectric thin film device

By using [C4N2H14][SbBr5] organic-inorganic hybrid materials, combined with hydrothermal reaction and spin-coating vacuum annealing process, photoelectric thin film devices with high light response speed and detection sensitivity were prepared, which solved the shortcomings of existing materials in environmental stability and performance adjustment, and achieved more efficient photoelectric conversion and stability.

CN119698215AActive Publication Date: 2025-03-25SHANGHAI INST OF TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411656224.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-03-25
Estimated Expiration
2044-11-19

AI Technical Summary

Technical Problem

In the preparation of photoelectric devices, existing organic-inorganic hybrid materials have poor environmental stability, complex synthesis process, limited performance tunability, interface effect problems and material design limitations, which are difficult to meet the needs of improving photoelectric conversion efficiency or enhancing carrier mobility.

Method used

[C4N2H14][SbBr5] is used as organic-inorganic hybrid photodetection material, and the material is prepared by hydrothermal reaction method, and the photoelectric thin film devices are prepared by spin coating, vacuum annealing and screen printing processes.

Benefits of technology

It improves the light response speed and detection sensitivity of optoelectronic thin film devices, enhances the stability and overall performance of the device, and is simple in process and easy to be produced in industrial form.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119698215A_ABST
    Figure CN119698215A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of photoelectricity, in particular to application of an organic-inorganic hybrid light detection material in preparation of a photoelectric thin film device. The method comprises the following steps: firstly, uniformly mixing an organic-inorganic hybrid light detection material, dimethyl sulfoxide and N, N-dimethylformamide to obtain a mixed solution; spin-coating a conductive substrate with the solution, and carrying out vacuum annealing treatment to obtain a photoelectric film; and finally, silver paste is printed on the photoelectric thin film through a silk screen, and the photoelectric thin film device is prepared. The chemical structural formula of the organic-inorganic hybrid light detection material is [C4N2H14] [SbBr5], and the organic-inorganic hybrid light detection material has the following unit cell parameters: # imgabs 0 # angle alpha is equal to 90 degrees, beta is equal to 118.763 (2) degrees, and gamma is equal to 90 degrees.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of optoelectronic technology, and in particular to the application of an organic-inorganic hybrid light detection material in the preparation of optoelectronic thin film devices. Background Art

[0002] With the rapid development of optoelectronic device technology, organic-inorganic hybrid materials have become an important research direction in the field of optoelectronic devices due to their unique structure, excellent optoelectronic properties and good adjustability. In particular, in the preparation of optoelectronic devices, these materials have become ideal candidate materials for efficient light energy conversion and storage due to their excellent properties such as low cost, easy synthesis, adjustable band gap, and nonlinear photoresponse. Research in the fields of photovoltaic cells, photoelectrocatalysis, sensors, and energy storage devices has shown that the rational design of organic-inorganic hybrid materials can significantly improve the photoelectric conversion efficiency, reduce energy loss, and enhance the stability and environmental adaptability of the device. However, the existing technology still faces many challenges, including poor environmental stability of materials, complex synthesis process, limited performance adjustability, interface effect problems, and limitations in material design. Existing organic-inorganic hybrid materials are prone to decay under harsh conditions such as high humidity, high temperature, and ultraviolet light, and the high cost and low yield in the synthesis process also limit their wide application. In addition, there are still certain bottlenecks in the performance adjustment of materials, which makes it difficult to meet special needs such as improving photoelectric conversion efficiency or enhancing carrier mobility. Summary of the invention

[0003] In order to solve the above problems, the purpose of the present invention is to provide an application of an organic-inorganic hybrid light detection material in the preparation of a photoelectric thin film device.

[0004] This application aims to solve the technical problems of environmental stability, synthesis process, performance adjustability and poor light absorption of organic-inorganic hybrid materials in the preparation of optoelectronic devices, so as to further improve the overall performance and application potential of optoelectronic devices. 14 As an organic-inorganic hybrid material, ][SbBr5] has good photoelectric properties and adjustability, and can provide new ideas for the research of optoelectronic devices.

[0005] The purpose of the present invention can be achieved by the following technical solutions:

[0006] The first object of the present invention is to provide an application of an organic-inorganic hybrid light detection material in the preparation of a photoelectric thin film device. The chemical structure of the organic-inorganic hybrid light detection material is [C4N2H 14 ][SbBr5], and has the following unit cell parameters: The angles are α=90°, β=118.763(2)°, and γ=90°.

[0007] In one embodiment of the present invention, the organic-inorganic hybrid photodetection material is prepared by the following method:

[0008] (S1) Sb2O3 and HBr are fully mixed to obtain a SbBr3 solution;

[0009] (S2) adding 1,4-diaminobutane to the SbBr3 solution obtained in step (S1), and performing post-treatment after hydrothermal reaction to obtain an organic-inorganic hybrid optical detection material.

[0010] Further, in step (S1), in step (S1), the ratio of Sb2O3 to HBr is 1mmol:3-8mL;

[0011] In step (S2), the ratio of 1,4-diaminobutane to SbBr3 solution is 1 mmol: 3-8 mL;

[0012] During the hydrothermal reaction, the temperature is 100-150°C and the time is 10-14h;

[0013] The post-treatment is centrifugation, washing and drying in sequence.

[0014] Furthermore, during the centrifugation process, the speed was 3000 r / min and the time was 20 s;

[0015] During the washing process, the detergent is ethyl acetate;

[0016] During the drying process, the temperature is 60°C and the time is 6 hours.

[0017] The second object of the present invention is to provide a method for preparing a photoelectric thin film device, which specifically comprises the following steps:

[0018] (A1) mixing an organic-inorganic hybrid photodetection material, dimethyl sulfoxide and N,N-dimethylformamide to obtain a mixed solution;

[0019] (A2) spin coating the solution prepared in step (A1) on a conductive substrate, and performing vacuum annealing to obtain a photoelectric thin film;

[0020] (A3) preparing a photoelectric thin film device by screen printing silver paste on the photoelectric thin film prepared in step (A2);

[0021] Among them, the chemical structure of the organic-inorganic hybrid photodetection material is [C4N2H 14 ][SbBr5], and has the following unit cell parameters: The angles are α=90°, β=118.763(2)°, and γ=90°.

[0022] In one embodiment of the present invention, in step (A1), the usage ratio of the organic-inorganic hybrid photodetection material, dimethyl sulfoxide and N,N-dimethylformamide is 1 g: 0.3-0.8 mL: 0.3-0.8 mL.

[0023] In one embodiment of the present invention, the usage ratio of the organic-inorganic hybrid photodetection material, dimethyl sulfoxide and N,N-dimethylformamide is 1 g: 0.5 mL: 0.5 mL.

[0024] In one embodiment of the present invention, in step (A2), during the vacuum annealing treatment, the temperature is 120-150° C. and the time is 0.5-1 h.

[0025] In one embodiment of the present invention, in step (A2), the thickness of the photovoltaic film is 3.21 to 3.68 μm;

[0026] Preferably, the thickness of the photovoltaic thin film is 3.68 μm.

[0027] The third object of the present invention is to provide a photoelectric thin film device prepared by the above method.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] (1) The prepared photoelectric film has uniform thickness, high density and good photoelectric response characteristics. The vacuum annealing treatment ensures that the lattice structure of the film is optimized, thereby enhancing the electron transport capacity and overall performance of the film.

[0030] (2) The method for preparing the photoelectric thin film device provided by the present invention prepares the organic-inorganic hybrid light detection material by a simple hydrothermal reaction method, and then prepares the photoelectric thin film device by spin coating, vacuum annealing and screen printing. The process flow is simple, the operability is strong, and it is easy to industrialize. The optimization of the temperature, time and other conditions in the steps ensures the quality of the materials and devices.

[0031] (3) The organic-inorganic hybrid photodetection material [C4N2H 14 ][SbBr5], with its specific crystal structure and good photoelectric properties, can effectively improve the light response speed and detection sensitivity of photoelectric thin film devices. Its excellent photoelectric properties make its application in photoelectric thin film devices more efficient and stable. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 The organic-inorganic hybrid photodetection material [C4N2H 14 XRD pattern of ][SbBr5];

[0033] Figure 2 The organic-inorganic hybrid photodetection material [C4N2H 14 [SbBr5] structure diagram (a);

[0034] Figure 3 The organic-inorganic hybrid photodetection material [C4N2H 14 [SbBr5] structure diagram (ii);

[0035] Figure 4 The organic-inorganic hybrid photodetection material [C4N2H 14 Optical photograph of ][SbBr5];

[0036] Figure 5 The organic-inorganic hybrid photodetection material [C4N2H 14 Absorption-bandgap diagram of ][SbBr5];

[0037] Figure 6 is a SEM cross-sectional view of the photovoltaic thin films of different thicknesses in Example 2;

[0038] Figure 7 is an IT curve diagram of photovoltaic films of different thicknesses in Example 2;

[0039] Figure 8 For [C4N2H in Example 4 14 IT curve of ][SbBr5] photoelectric material at different polarization voltages. DETAILED DESCRIPTION

[0040] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0041] In the following examples, unless otherwise specified, all reagents used are commercially available reagents, and all detection means and methods used are conventional detection means and methods in the art.

[0042] Example 1

[0043] This embodiment provides a hydrothermal synthesis method of an organic-inorganic hybrid light detection material, which specifically includes the following steps:

[0044] (S1) Sb2O3 and HBr solvent are uniformly mixed to obtain a SbBr3 solution.

[0045] The dosage ratio of Sb2O3 to HBr is 5mmol:25mL;

[0046] (S2) adding 5 mmol of 1,4-diaminobutane to the SbBr3 solution obtained in step (S1), stirring and mixing to obtain a mixed solution;

[0047] (S3) The mixture prepared in step (S2) is transferred to a reaction vessel and subjected to a hydrothermal reaction (temperature of 120° C., time of 12 h).

[0048] (S4) The product obtained after the hydrothermal reaction in step (S3) was centrifuged (speed of 3000 r / min, time of 20 s), the precipitate was collected, and the precipitate was washed with ethyl acetate, and then the washed product was placed at 60 ° C. and dried for 6 h to obtain an organic-inorganic hybrid optical detection material: [C4N2H 14 ][SbBr5](rod-shaped, purity 98%).

[0049] Performance testing and result analysis:

[0050] In this embodiment, the prepared organic-inorganic hybrid optical detection material [C4N2H 14 ][SbBr5] was tested and the results were as follows Figure 1 As shown, the obtained sample is a single phase. In the test, the graphite monochromatized Mo Kα radiation (wavelength ), and collected single crystal X-ray diffraction data by ω-2θ scanning method. According to the room temperature single crystal XRD data analysis, the material exhibits a polar monoclinic structure of P21 space group, and its crystal structure is composed of one-dimensional angle-sharing SbBr6 octahedral chains along the b-axis and independent 1.4-diaminobutane molecules. The structural schematic diagram is shown in Figure 2 and Figure 3 shown.

[0051] Table 1 [C4N2H 14 Unit cell parameters of [SbBr5] organic-inorganic hybrid photodetection material crystal

[0052]

[0053] In addition, optical microscopy observation of [C4N2H 14 [SbBr5] single crystal morphology (see Figure 4 ) and found that the material was yellow rod-shaped with a smooth surface and no obvious defects. The optical absorption properties and band gap of the single crystal material were measured using a UV-visible-near infrared spectrophotometer (see Figure 5 ), the results showed that the absorption edge of the material is at 506nm and the optical band gap is 2.58eV.

[0054] Example 2

[0055] This embodiment provides a method for preparing an organic-inorganic hybrid light detection material photoelectric thin film, which specifically includes the following steps:

[0056] (1) 0.3 g of [C4N2H14 [SbBr5] single crystal powder was dissolved in 0.3 mL DMSO and DMF solution (the volume ratio of DMSO and DMF was 1:1), and the mixture was stirred thoroughly to make [C4N2H 14 The [SbBr5] single crystal powder is completely dissolved to obtain a mixed solution;

[0057] (2) Spin coating the mixed solution prepared in step (1) on an ITO conductive substrate to form a film, with a spin coating amount of 50 μL / time, a spin coater speed of 3000 rpm, a spin coating time of 30 s, and spin coating once, three times, five times, eight times, and ten times to obtain spin-coated samples;

[0058] The obtained spin-coated sample was placed in a tube furnace, heated to 120°C at a rate of 1°C / min, calcined in vacuum for 0.5h, and then cooled in vacuum to room temperature to obtain [C4N2H 14 ][SbBr5] photoelectric thin films (the thickness of the obtained photoelectric thin films were 2.73μm, 3.21μm, 3.68μm, 4.48μm and 5.76μm respectively);

[0059] (3) The [C4N2H 14 By screen printing silver paste (as the back electrode) on the [SbBr5] photovoltaic film, [C4N2H 14 ][SbBr5] photoelectric thin film device: from bottom to top, it includes ITO conductive substrate, [C4N2H 14 ][SbBr5] thin film and Ag electrode.

[0060] In this example, five different thicknesses of [C4N2H 14 [SbBr5] photoelectric thin film, [C4N2H 14 The thickness of the [SbBr5] film can be estimated from its SEM cross-sectional image (see Figure 6 ) The current-time (It) curve related to thickness is as follows Figure 7 shown.

[0061] pass Figure 6 and Figure 7 It can be found that as the thickness of the photoelectric film increases, the photocurrent density first increases, reaching a maximum value of 63pA at 3.68μm, and then decreases as the thickness of the photoelectric film further increases. This is because the recombination rate of photogenerated carriers increases significantly in thicker photoelectric films, especially when the thickness of the photoelectric film exceeds a certain critical value. At this time, the diffusion time of photogenerated carriers in the film increases, and they may recombine with defects or impurities before reaching the electrode, resulting in a decrease in the effective carrier concentration. Therefore, [C4N2H 14The optimal thickness of the ][SbBr5] photoelectric film was fixed as 3.68 μm for further photoelectric measurements.

[0062] Example 3

[0063] This embodiment provides a method for preparing an organic-inorganic hybrid light detection material photoelectric thin film, which specifically includes the following steps:

[0064] (1) 0.3 g of [C4N2H 14 [SbBr5] single crystal powder was dissolved in 0.3 mL DMSO and DMF solution (the volume ratio of DMSO and DMF was 1:1), and the mixture was stirred thoroughly to make [C4N2H 14 The [SbBr5] single crystal powder is completely dissolved to obtain a mixed solution;

[0065] (2) Spin coating the mixed solution prepared in step (1) on an ITO conductive substrate to form a film, with a spin coating amount of 50 μL / time, a spin coater speed set to 3000 rpm, a spin coating time of 30 s, and spin coating 5 times to obtain a spin coating sample;

[0066] The obtained spin-coated sample was placed in a tube furnace, heated to 150°C at a rate of 1°C / min, calcined in vacuum for 1 h, and then cooled in vacuum to room temperature to obtain [C4N2H 14 [SbBr5] photoelectric thin film (thickness 3.68μm);

[0067] (3) The [C4N2H 14 By screen printing silver paste (as the back electrode) on the [SbBr5] photovoltaic film, [C4N2H 14 ][SbBr5] photoelectric thin film device: from bottom to top, it includes ITO conductive substrate, [C4N2H 14 ][SbBr5] thin film and Ag electrode.

[0068] In this embodiment, the prepared photoelectric thin film device was tested using a 4200A-SCS digital source meter under the irradiation of a 500W (AM 1.5G) xenon lamp. Under zero bias voltage conditions, the current of the photoelectric thin film device showed a changing trend as the applied voltage changed. Specifically, the photocurrent showed a trend of first increasing and then decreasing with the increase of the polarization voltage. Under the negative polarization state, when a voltage of -8V was applied, the measured photocurrent peak was 223.6pA; and under the positive polarization state, when a voltage of 8V was applied, the photocurrent peak was -158.4pA. Therefore, under the -8V voltage condition, the best photocurrent response (such as Figure 8 Show).

[0069] Comparative Example 1

[0070] This comparative example provides a method for preparing an organic-inorganic hybrid light detection material photoelectric thin film, which specifically comprises the following steps:

[0071] (1) 0.3 g of [C4N2H 14 ][SbBr5] single crystal powder was dissolved in 0.3 mL DMSO solution and stirred thoroughly to make [C4N2H 14 The [SbBr5] single crystal powder is completely dissolved to obtain a mixed solution;

[0072] (2) Spin coating the mixed solution prepared in step (1) on an ITO conductive substrate to form a film, with a spin coating amount of 50 μL / time, a spin coater speed set to 3000 rpm, a spin coating time of 30 s, and spin coating 5 times to obtain a spin coating sample;

[0073] The obtained spin-coated sample was placed in a tube furnace, heated to 120°C at a rate of 1°C / min, calcined in vacuum for 0.5h, and then cooled in vacuum to room temperature to obtain [C4N2H 14 ][SbBr5] photoelectric film (its thickness is controlled to be 3.68 μm, but the photoelectric film is uneven, has poor crystallinity, and is not flat);

[0074] (3) The [C4N2H 14 By screen printing silver paste (as the back electrode) on the [SbBr5] photovoltaic film, [C4N2H 14 ][SbBr5] photoelectric thin film device: from bottom to top, it includes ITO conductive substrate, [C4N2H 14 ][SbBr5] thin film and Ag electrode.

[0075] The results showed that [C4N2H 14 [SbBr5] single crystal powder cannot be well dissolved in DMSO solution, making the produced film uneven, with poor crystallinity and unevenness, which affects the optical properties of the film.

[0076] Comparative Example 2

[0077] This comparative example provides a method for preparing an organic-inorganic hybrid light detection material photoelectric thin film, which specifically comprises the following steps:

[0078] (1) 0.3 g of [C4N2H 14 [SbBr5] single crystal powder was dissolved in 0.3 mL DMF solution and stirred thoroughly to make [C4N2H 14 The [SbBr5] single crystal powder is completely dissolved to obtain a mixed solution;

[0079] (2) Spin coating the mixed solution prepared in step (1) on an ITO conductive substrate to form a film, with a spin coating amount of 50 μL / time, a spin coater speed set to 3000 rpm, a spin coating time of 30 s, and spin coating 5 times to obtain a spin coating sample;

[0080] The obtained spin-coated sample was placed in a tube furnace, heated to 120°C at a rate of 1°C / min, calcined in vacuum for 0.5h, and then cooled in vacuum to room temperature to obtain [C4N2H 14 ][SbBr5] photoelectric film (its thickness is controlled to be 3.68 μm, but the photoelectric film is uneven, has poor crystallinity, and is not flat);

[0081] (3) The [C4N2H 14 By screen printing silver paste (as the back electrode) on the [SbBr5] photovoltaic film, [C4N2H 14 ][SbBr5] photoelectric thin film device: from bottom to top, it includes ITO conductive substrate, [C4N2H 14 ][SbBr5] thin film and Ag electrode.

[0082] The results showed that [C4N2H 14 [SbBr5] single crystal powder cannot be well dissolved in DMF solution, and the film appears as granular powder with poor film density, which affects the optical properties of the film.

[0083] By comparing Comparative Example 1, Comparative Example 2 and Example 2, it was found that a mixed solution of DMF and DMSO (the volume ratio of DMF and DMSO was 1:1) could dissolve [C4N2H 14 ][SbBr5] single crystal powder. This measure breaks the conventional cognition of technicians in this field. This may be because DMF has a stronger hydrogen bond accepting ability, while DMSO has a stronger hydrogen bond donor ability. The mixture of the two can form a more diverse hydrogen bond network, which enhances the hydrogen bond of [C4N2H 14 Solubility of ][SbBr5] single crystal powder.

[0084] Comparative Example 3

[0085] This comparative example provides a method for preparing an organic-inorganic hybrid light detection material photoelectric thin film, which specifically comprises the following steps:

[0086] (1) 0.3 g of [C4N2H 14 [SbBr5] single crystal powder was dissolved in 0.3 mL DMSO and DMF solution (the volume ratio of DMSO and DMF was 1:1), and the mixture was stirred thoroughly to make [C4N2H 14The [SbBr5] single crystal powder is completely dissolved to obtain a mixed solution;

[0087] (2) spin coating the mixed solution prepared in step (1) on an ITO conductive substrate to form a film, and then dropping 10 μL of the mixed solution onto the ITO conductive substrate by scraping to obtain a photoelectric thin film;

[0088] The obtained photovoltaic film was placed in a tube furnace, heated to 120°C at a rate of 1°C / min, calcined in vacuum for 0.5h, and then cooled in vacuum to room temperature to obtain [C4N2H 14 ][SbBr5] photoelectric thin film;

[0089] (3) The [C4N2H 14 By screen printing silver paste (as the back electrode) on the [SbBr5] photovoltaic film, [C4N2H 14 ][SbBr5] photoelectric thin film device: from bottom to top, it includes ITO conductive substrate, [C4N2H 14 ][SbBr5] thin film and Ag electrode.

[0090] The results show that the photoelectric film prepared in this comparative example has uneven thickness, poor photoelectric performance, and poor stability. The minimum thickness of the photoelectric film prepared by the scraping method is 7μm. After an annealing time of 0.5h, the defects in the film cannot be effectively repaired, resulting in a decrease in electron mobility, thereby affecting the overall photoelectric conversion efficiency.

[0091] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the explanation of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. An application of an organic-inorganic hybrid light detection material in the preparation of a photoelectric thin film device, characterized in that: The chemical structure of organic-inorganic hybrid photodetection material is [C4N2H 14 ][SbBr5], and has the following unit cell parameters: The angles are α=90°, β=118.763(2)°, and γ=90°.

2. The use according to claim 1, characterized in that: The organic-inorganic hybrid light detection material is prepared by the following method: (S1) Sb2O3 and HBr are fully mixed to obtain a SbBr3 solution; (S2) adding 1,4-diaminobutane to the SbBr3 solution obtained in step (S1), and performing post-treatment after hydrothermal reaction to obtain an organic-inorganic hybrid optical detection material.

3. The use according to claim 2, characterized in that: In step (S1), the ratio of Sb2O3 to HBr is 1mmol:3-8mL; In step (S2), the ratio of 1,4-diaminobutane to SbBr3 solution is 1 mmol: 3-8 mL; During the hydrothermal reaction, the temperature is 100-150°C and the time is 10-14h; The post-treatment is centrifugation, washing and drying in sequence.

4. A method for preparing a photoelectric thin film device, characterized in that: The specific steps include: (A1) mixing an organic-inorganic hybrid photodetection material, dimethyl sulfoxide and N,N-dimethylformamide to obtain a mixed solution; (A2) spin coating the solution prepared in step (A1) on a conductive substrate, and performing vacuum annealing to obtain a photoelectric thin film; (A3) preparing a photoelectric thin film device by screen printing silver paste on the photoelectric thin film prepared in step (A2); Among them, the chemical structure of the organic-inorganic hybrid photodetection material is [C4N2H 14 ][SbBr5], and has the following unit cell parameters: The angles are α=90°, β=118.763(2)°, and γ=90°.

5. The method for preparing a photoelectric thin film device according to claim 4, characterized in that: In step (A1), the usage ratio of the organic-inorganic hybrid optical detection material, dimethyl sulfoxide and N,N-dimethylformamide is 1 g: 0.3-0.8 mL: 0.3-0.8 mL.

6. The method for preparing a photoelectric thin film device according to claim 5, characterized in that: The usage ratio of the organic-inorganic hybrid optical detection material, dimethyl sulfoxide and N,N-dimethylformamide is 1 g: 0.5 mL: 0.5 mL.

7. The method for preparing a photoelectric thin film device according to claim 4, characterized in that: In step (A2), during the vacuum annealing treatment, the temperature is 120-150° C. and the time is 0.5-1 h.

8. The method for preparing a photoelectric thin film device according to claim 4, characterized in that: In step (A2), the thickness of the photovoltaic film is 3.21 to 3.68 μm.

9. The method for preparing a photoelectric thin film device according to claim 8, characterized in that: The thickness of the photovoltaic film is 3.68 μm.

10. A photoelectric thin film device, characterized in that: It is prepared by the method described in any one of claims 4 to 9.

Citation Information

Patent Citations

  • Novel viologen-based organic-inorganic hybrid photoconductive material, and preparation method and application thereof

    CN116199620A

  • Antimony-based perovskite single crystal, preparation method thereof, semiconductor material and X-ray detector

    CN118048690A

  • Techniques for Forming a Chalcogenide Thin Film Using Additive to a Liquid-Based Chalcogenide Precursor

    US20130312831A1

  • Process for forming a doped oxide film and doped semiconductor

    US4605450A